Introduction [EN] (Signifiances (Signifying), 2017)
This first volume of the journal Signifiances (Signifying) brings together the written texts of the 1st International Conference Language and Enaction – Sense-making, embodiment, interaction, organized in Clermont-Ferrand from the 1st to the 3rd June 2016 (LangEnact 1). The growing interest for enaction among linguists, researchers on didactics, and specialists in other fields of research related to language was a sign to promote this conference. This meeting also aimed at making researchers specialized in convergent fields interact with each other. In this respect, we would like to thank the participants of the conference Langenact 1 and all our partners, through whom the crystallization of the multi-disciplinary approach « Language and Enaction » is starting to show. The recent projects and the on-going prospects pertaining to the conference Langenact 2 (25-27 September 2017) organized at the University of Southern Danemark (Odense) and the thematic issue to appear in December 2017 in the journal Intellectica (n°68) make new collaborations stronger among researchers who had not known each other until very recently. A greater scientific communication is coming up.